Three-dimensional evaluation of the maxillary dentoalveolar changes with three different intraoral distalization systems: Jones Jig, Distal Jet and First Class - Pereira, Sílvio Augusto Bellini (2019)
Introduction: To compare the maxillary dentoalveolar changes of patients treated with three distalization force systems: Jones Jig, Distal Jet and First Class, using digitized models. Material and Methods: The sample comprised 51 patients with Class II malocclusion divided into three groups: Group 1 consisted of 17 patients treated with the Jones Jig appliance; Group 2 consisted of 17 patients treated with the Distal Jet, and Group 3 comprised 17 patients treated with the First Class. Initial and postdistalization plaster models of all patients were digitized and evaluated in the OrthoAnalyzerTM software. The initial and post-distalization measurements regarding sagittal, rotational and transverse changes were compared by the One-way Analysis of Variance (ANOVA) and Kruskal-Wallis tests, depending on normality. Results: All appliances presented similar amounts of distalization and anchorage loss. The Distal Jet appliance promoted significantly smaller mesial displacement of premolars and greater expansion of posterior teeth. The First Class presented the smallest rotation of the maxillary molars and treatment time. Conclusion: The distalizers were effective in correcting a Class II molar relationship, however, a palatal force seems to provide fewer undesirable effects. Additionally, the degree of rotation and expansion is associated with the side of force application.